A Threat to Global Food Security - Otero Justo, Manuel Rodolfo (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
South America is facing its worst drought in a century due to the La Niña phenomenon that started in 2020. The most affected countries are Argentina, Brazil, Paraguay, and Uruguay, which are major producers of food and fiber for the world. These countries account for approximately 13% of global food and fiber exports, and their production losses directly impact global food markets and security. The article highlights the devastating effects of drought on crops, livestock, and the economy of the affected regions. It also urges developed countries to fund mechanisms to strengthen agriculture sectors vulnerable to climate change and support policies to deal with agricultural emergencies.